Seleksi Sel Bakteri Dari Minyak Bumi Sebagai Molekul Pengenal Dalam Biosensor Benzena - Alfiah Alif; Dyah Iswantini; Henny Purwaningsih; Novik Nurhidayat; Amalyah Febryanti (Al-Kimia, 2021)
Benzene is one of the harmful compounds which can affect both healthcare and environmental quality. Conventionally the effort of detecting this compound still requires several sample pre-treatments, contributing to a long analysis time and sophisticated instrumentation. Therefore, this study was aimed to determine the potency of bacteria as the bioreceptor for detecting benzene electrochemically. The bacteria isolate was immobilized on the working electrode surface. Four bacteria isolates from the petroleum sample were evaluated. The results showed that isolate II produced high oxidation and reduction peak currents as much as 150 µA and -490 µA respectively. The selected bacteria showed characteristics to Pseudomonas sp. physiologically. Since the bacteria can degrade benzene, thus hypothetically it can produce benzene dioxygenase. Through the catechol formation, 3 mM benzene produced 108.7 µA after 11.4 s from the starting scan. This result suggested that the excreted enzyme from the selected bacteria could react with benzene enzymatically.